Pain Type and Quality of Life in Cervicogenic Headache Patients - Sudibyo, Devi Ariani; Fathoni, M Reza; Puti, Nazla Ananda Rachmi (AKSONA, 2025)
Highlight: Cervicogenic headache is the most incapacitating type, leading to significant physical impairment. Based on the data, there were 15 subjects in the nociceptive pain group and 15 subjects in the neuropathic pain group. There was a statistically significant correlation between the type of pain and the mental quality of life. In patients with cervicogenic headaches and neuropathic pain, there was a stronger relationship than those with nociceptive pain.   ABSTRACT Introduction: Cervicogenic headache is classified as a secondary headache under the International Classification of Headache Disorders, third edition (ICHD-3). Significant neuropathic and nociceptive pain components are believed to be present in this condition, which eventually lowers quality of life by causing problems like anxiety, depression, and sleep disruptions. Objective: This study aimed to correlate pain types with quality of life in those suffering from cervicogenic headaches. Methods: A cross-sectional observational study was conducted at the Neurology Outpatient Clinic of Dr. Soetomo General Academic Hospital in Surabaya from June to August 2020. Quality of life and pain types were evaluated using the painDETECT and SF-36 questionnaires. A painDETECT score of 12 or less indicated nociceptive pain, but a score of more than 12 indicated neuropathic pain. An SF-36 score below 50 indicated a poor quality of life. Conclusion:Patients with cervicogenic headaches and neuropathic pain exhibited a lower quality of life compared to those experiencing nociceptive pain. These findings emphasize the importance of evaluating pain types to support the maintenance of a good quality of life.